Gestational Surrogacy dalam Islam dan Implikasi Hukum Syariah - M. Rifky Syahmanda; Muhammad Wijdan Wiradibrata; Ghifari Muttaqien Dermawan Pramono (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
Gestational surrogacy is a form of surrogacy in which a woman carries and gives birth to a child without any genetic relationship to the baby. In this process, the egg from the biological mother and the sperm from the biological father are combined through in vitro fertilization (IVF), and the resulting embryo is implanted into the surrogate mother's womb. After giving birth, the surrogate mother hands the baby over to the couple or individual who arranged the surrogacy, in exchange for financial compensation for her service. Although gestational surrogacy offers several benefits, this practice raises numerous questions from an Islamic perspective, such as its legality, the lineage of the child born, and the social and ethical impact it has on the Muslim community. This paper focuses on analyzing Islamic views on gestational surrogacy and the accompanying implications of Sharia law. The article employs a qualitative method with discussions covering the definition of surrogacy from an Islamic perspective, Sharia legal analysis of surrogacy practices, as well as the social and ethical impact that arises in the Muslim community.